Globalization, Productivity Growth, and Labor Compensation - Christian Dreger; Marius Fourné; Oliver Holtemöller (Institute of Labor Economics (IZA), 2023)
We analyse how changes in international trade integration affect productivity and the functional income distribution. To account for endogeneity, we construct a leave-out measure for international trade integration for country-industry pairs using international input-output tables. First, we corroborate on the country-industry level that international trade integration increases productivity. Second, we show that international trade integration is associated with higher labour shares in advanced countries but with lower labour shares in manufacturing industries in emerging markets. Finally, we briefly discuss the implications of our results for a possible throwback in international trade integration due to experiences from recent crises.
Keywords: F4; F6; J3; 330; global value chains; income distribution; globalization; labor share; productivity